Kinematics and Workspace Analysis of Parallel Manipulators - Bodnár, Dávid; Hajdu, Sándor (International Journal of Engineering and Management Sciences, 2018)
The aim of the study is to analyse the kinematics and the workspaces of two parallel manipulators. The kinematics are calculated using vectors and the Newton method. The workspaces are shown using constant orientation. The result of the study is that the kinematics and workspaces are comparable of the two manipulators. MATLAB was used for calculating.